2015
DOI: 10.5897/ajar2015.10029
|View full text |Cite
|
Sign up to set email alerts
|

Study of potential environmental risk of trace metallic elements in mine tailings: Case of Draa Lasfar functional mine in Marrakech - Morocco

Abstract: Mining activity is one of the most important sources of heavy metals in the environment. In Marrakech region, functioning or abandoned mines represent a great hazard due to huge amounts of waste deposited in waste dumps and tailings often with high concentration of heavy metals pollution. In this study, the chemical forms of four heavy metals in mine tailings of Draa Lasfar in north-west of Marrakech city (Morocco) were studied by determining of four metals (Cd, Cu, Pb, and Zn) using standard solvent extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In Morocco, Yassir et al, 2015, studied the different associations of Cd, Cu, Pb and Zn in the mine tailings of the Draa Lasfar mine. The results suggested that Cd and Cu were mainly associated with a more mobile fraction, Pb with a less mobile fraction and Zn was essentially bound to Fe-Mn oxides [13]. The study of Pourret et al, 2016, was focused in the analysis of the fractionation and mobility of Co and Cu in contrasting soils (soils, mine tailings, smelting waste disposal) from the Katanga mine [14].…”
Section: Introductionmentioning
confidence: 99%
“…In Morocco, Yassir et al, 2015, studied the different associations of Cd, Cu, Pb and Zn in the mine tailings of the Draa Lasfar mine. The results suggested that Cd and Cu were mainly associated with a more mobile fraction, Pb with a less mobile fraction and Zn was essentially bound to Fe-Mn oxides [13]. The study of Pourret et al, 2016, was focused in the analysis of the fractionation and mobility of Co and Cu in contrasting soils (soils, mine tailings, smelting waste disposal) from the Katanga mine [14].…”
Section: Introductionmentioning
confidence: 99%